IMPROVING STUDENTS’ SPEAKING SKILL FOR GENERAL COMMUNICATION THROUGH ENGLISH MOVIE (A Study at the Third Semester Students of Polytechnic Unggul LP3M - Handayani, Cici (JURNAL ILMU PENDIDIKAN, 2024)
Students in Polytechnic Unggul LP3M especially in 3rd Semester has Speaking for general communication as compulsory subject. Even in higher education, there are some lakcness in reality, most of the students face some problems in speaking. The lecturer used Collaborative Classroom Action Research (CAR) to find out what media is the most suitable for the students so it can be used to improve the students’ speaking ability. The objectives of the study are: 1) finding out whether or not English Movie can improve the students’ speaking skill 2) finding out classroom situation when English Movie implemented in speaking class. To collect data, the researcher used instruments of observations, tests and questionnaires. The finding showed that the use of English Movie was effective in improving the speaking abilities of the student in class. This can be seen from the improvements after each cycle. The average score of pre-test was 65.92. After the implementation of English Movie in every cycle, the students’ speaking score were getting better. It can be seen from the result of students’ average score 73.26 in cycle 1 and 82,2 in cycle 2. The atmosphere of the class was more lively as there are many interesting activities with relax feeling, They enjoy for various types of activities related to English Movie. The student gave attention to the lessons they were very active to conduct the activities and dominated the activities. They were not afraid of making mistakes